The Valuation of Nonsystematic Risks and the Pricing of Swedish Lottery Bonds - Green, Richard C.; Rydqvist, Kristian (Review of Financial Studies, 1997)
Swedish government lottery bonds have coupon payments determined by lottery. They offer a unique opportunity to study a security with uncertain payoffs having a known, observable distribution. The risk associated with the lotteries is idiosyncratic by construction and should not command a risk premium in equilibrium. The bonds are traded in two forms, allowing us to evaluate the rewards to bearing extra lottery risk. Despite its idiosyncratic nature, we find prices appear to reflect aversion to this risk. We evaluate the empirical determinants of this differential pricing and possible explanations for it.